EFFECT OF DIETARY SUPPLEMENTATIONS ON BODY CONDITION SCORE, OCCURRENCE OF POST PARTURIENT DYSGALACTIA SYNDROME, LITTER PERFORMANCE AND SERUM BIOCHEMICAL PROFILE IN TRANSITION SOWS - PATRA, MANAS KUMAR; KUMAR DE, UJJWAL; KENT, YHUNTILO; RUNGSUNG, SOYA (The Indian Journal of Animal Reproduction, 2021)
The aim of the present study was to investigate the effect of different dietary supplementations in periparturientsow diet on the occurrence of post parturient dysgalactia syndrome (PDS), body condition score (BCS), litterperformance and serum biochemical profile. Forty-eight pregnant multiparous crossbred sows (Hampshire × Ghungroo)were randomly divided into four groups (12 sows per group) 30 days before expected date of farrowing as control(Basal diet); probiotics (Basal diet + Probiotics); Vitamin E-selenium and aminoacids (Basal diet + VES-AA) andcalcium-vitamin (Basal diet + Cal-Vit). The results of the study revealed that the occurrence of PDS was lowest(p
Keywords: sows; dysgalactia; supplementation; litter performance; body condition score